Development of Scientific Based Learning Video Media Using Problem Based Learning (PBL) Model to Improve Student Learning Outcomes in 4Th Grade Students of Elementary School Parmaksian, Kab. Toba Samosir - Launa Yenny Abadi Simanjuntak; Reh Bungana Perangin-Angin; Daulat Saragi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Learning media is a learning tool that is very important in the learning process. This study aims to produce scientific-based learning videos with problem-based learning models to improve the learning outcomes of Civic students in 4th grade elementary school in Parm testimonial, Toba Samosir district. This type of research is research and development using the 4D model. research instruments used in the form of an expert validation questionnaire, teacher and student response questionnaire and learning achievement tests. Then the data analysis in the form of expert validation analysis is carried out by material, language and media experts, practicality analysis is carried out by teacher and student questionnaires and effectiveness analysis is done by pretest and posttest. The stages of this research are define, design, develop and assess. The results of this study indicate that the validation rate of material experts is 80% in the very high category, the validation of linguists is 89% in the very high category and the validation of the media expert is 92% in the very high category while the N gain for student learning outcomes is 0.7 with the category high. Finally, instructional videos are also considered by teachers and students by obtaining 87.5% of teachers and obtaining an average of 79% of students in either category. Thus, scientific-based videos can improve student learning outcomes.